(3MGTjI Ydi TQM HGfJ SYGO dGHf gTGe GdCfUGQjs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3GHf gTGe , YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa, LeGd GdOjf , CHh eMeO,J (B761 (3g` s ((3eMeO GdbWQj s)
(3ChdgG (B:s
(3CeG HYO(B: (3ajbhd YHOGdbGOQ Hf YeQ GdHZOGOj HYV GdENhGf TQM bUjOI HGfJ SYGO dcYH Hf RgjQ GdUMGHj ddEeGe YHOGddg Hf jhSa GdTgjQ HGHf gTGe s
(3BNQgG (B:s
(3hPcQg CjVkG aj ehGVY HYOg hgPG BNQ eG CQOfG EjVGMg LYdg Gddg NGdUkG dhLgg GdcQje s
(3HChdgG agQS dCHjGJ GdThGgO eQJHkG Ydi MQha GdeYLes
(3hBNQ ddYdeGA hGdTYQGA GdeJQLe dges
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B163 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B465s
Keywords: (3GdCOHs